Comments on editorial in American Medical Association Journal, 25 September 1948 - Journal of the American Medical Association (1948)
1948 1948 1940s 2 pages Comments on Editorial in American Medical Association Journal, 25th September, 1948. The Journal seeks to discredit proposals for a nation-wide sickness insurance plan in the United States by an attack on our National Health Service here in Great Britain. Before dealing with these charges, it should be made clear that our National Health Service, although part of the general social security plan, is not based on an insurance principle. National Health Insurance providing both cash benefits and a limited range of medical treatment was introduced into this country in 1912, when attacks similar to those now made by the A.M.A. Journal were made from various quarters, but despite the opposition of critics National Health Insurance developed into a system which conferred numerous benefits on the insured population. The new Health Service has abandoned the insurance principle and provides a full range of medical treatment for everybody without insurance conditions. Experience of the old scheme amply justified this development. We are told that "the greatest folly in the world is the manner in which Great Britain embarked in a nation-wide Health Service without hospitals, doctors, nurses, drugs or money." So far as hospitals are concerned, is the Editor of the Journal acquainted with the following facts incontestably established by numerous hospital surveys made before and during the war :- That hospital accommodation was gravely deficient in both quantity and quality? That the existing hospital services were completely unco-ordinated? That one-third of the beds in our so-called voluntary hospitals were in places with less than 100 beds which, with certain exceptions, were not in a position to give their patients the resources of modern medicine and surgery? Faced with this position, it was, according to the Journal, "the greatest folly in the world" to ensure, by the setting up of a National Health Service, that the great work of hospital development and construction which now has to be undertaken should proceed on a planned and co-ordinated basis. In fact, the existing system of hospital administration (or rather the patchwork of unco-ordinated systems) was quite incapable of doing the job. The stern test of war conditions had already shown that this was so. At that time, when large-scale air attacks demanded the highest efficiency and co-ordination of all available resources, the need for nation-wide hospital planning was universally recognised and embodied in the Emergency Hospital Service. As Lord Moran, a distinguished leader of British medical opinion, has recently written, "It was the war which, by rubbing the nation's nose in the facts, prepared it for reform and educated many in the medical profession to accept change." The Journal blandly assures its readers that "the unfortunate public have no means of knowing whether or not what they get is good medical service." Let us test this statement in relation to fracture treatment, a matter of first-class importance to the Trade Union Movement. In the years before the war, we were gravely concerned at the lack of uniformity in the treatment available. Scientific research gave startling support to our criticisms by establishing that only one per cent. of patients in a consecutive series treated at organised clinics remained permanently incapacitated, whereas thirty-seven per cent. of another series, including a proportion who had been treated at general hospitals without an organised clinic, remained permanently incapacitated. During and since the war there have been notable advances in this field, and we are convinced by past experience that it is only by the co-ordination of planning made possible by a National Service that these improvements can be maintained and developed. Men and women suffering the effects of permanent, preventable incapacity are not likely to share the Journal's view. 292/847/5/102